Routledge encyclopedia of translation studies [ - Baker, Mona; Saldanha, Gabriela (London New York : Routledge, 2009)
Presents a comprehensive overview of the academic discipline of translation studies. This book covers the history of translation in major linguistic/cultural communities, and a range of fresh entries, including the Irish, Korean and South African traditions. It is suitable for students and teachers of translation, interpreting and literary theory
Description based on print version record
Includes bibliographical references (p 561-659) and index
Keywords: Translating and interpreting -- Encyclopedias